Efeito do repolimento após clareamento na estabilidade de cor e rugosidade de resinas compostas - Rodrigues, Camila da Silva (2016)
This study aimed to evaluate the effect of repolishing after bleaching on color stability and roughness of two composite resins aged in high staining beverage. Sixty-one disc-shaped specimens (8 mm diameter x 2 mm thickness) of each composite resin were fabricated (microhybrid vs. nanoparticle), then divided according to treatment: bleached or non-bleached. After bleaching phase, groups were subdivided according to surface treatment, repolished or unrepolished, using extrafine sandpaper discs and felt with diamond paste. A new subdivision was performed according to aging conditions: immersion in red wine 15 min/day or in artificial saliva 24 h/day during 30 days. Color (CIE L*a*b* system) and roughness (Ra) were assessed at baseline (P0), after bleaching procedures (P1), after surface treatment (P2) and after aging (P3). Color change (ΔE00) was calculated with CIEDE2000 formula. One specimen per group was removed from each study phase, in order to be analyzed in Scanning Electron Microscope (SEM). Statistical analysis was performed using repeated measures ANOVA and Tukey s test as post-hoc (significance level was set at 5%). Bleached repolished groups presented lower color alteration than the bleached unrepolished groups of both composite resins when aged in red wine. Repolishing (P1 vs. P2) promoted a decrease in roughness values of almost all groups. Nanoparticle resin presented greater ΔE00 values than microhybrid one when aged in red wine. SEM images reveled more porosities in bleached unrepolished groups. Therefore, repolishing immediately after bleaching improves color stability of composite resins when exposed to staining agents, and it is capable to improve smoothness.